2018
DOI: 10.7150/jbji.28146
|View full text |Cite
|
Sign up to set email alerts
|

Successful Debridement of a Knee Joint Prosthesis Infected with Listeria Monocytogenes. Case Report and Review of Current Literature

Abstract: According to the relevant literature, prosthetic joint infections caused by Listeria monocytogenes require two stage revision surgery or prosthesis removal for a successful outcome. We present the case of a patient who suffered such an infection after Total Knee Replacement surgery and was successfully treated with antibiotics, joint lavage, debridement and retention of the prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In a recent study of 294 hips and knees, infection caused by LM was reported at a rate of 0.7%. We have found 67 cases with PJI caused by LM in English Literature (from 1987 until 2020) [ 2 , 3 , 5 , 20 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ] ( Table 1 ). The mid-time from initial surgery to the onset of infection caused by LM in the prior literature was 6.8 years (range, 2 mo-21 y) whereas in this case was 9 years postoperatively ( Table 1 , Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study of 294 hips and knees, infection caused by LM was reported at a rate of 0.7%. We have found 67 cases with PJI caused by LM in English Literature (from 1987 until 2020) [ 2 , 3 , 5 , 20 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ] ( Table 1 ). The mid-time from initial surgery to the onset of infection caused by LM in the prior literature was 6.8 years (range, 2 mo-21 y) whereas in this case was 9 years postoperatively ( Table 1 , Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Search results were limited to articles written in the English-language. There were 33 publications; 31 were found in PubMed and 2 in Google Scholar where 67 cases were reported (the first one was reported in 1987 and the last one was reported in 2020) ( Table 1 ) [ 2 , 3 , 5 , 20 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. The median age of the patients was 65 y (range, 29-87 y), there were ∼60% males and ∼40% females, 20 patients (30%) had TKA infection whereas 47 patients (70%) had THA infection including our case.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations